COMPARISON THE EFFECT OF GYMNASTICS ELDERLY AND WALKING ON DECREASE IN BLOOD PRESSURE OF PATIENTS HYPERTENSIVE IN THE POSYANDU ELDERLY KARAH - churniawan, hendry; Kumaat, Noortje Anita (Jurnal Kesehatan Olahraga, 2019)
Abstract Hypertension has become a major problem in elderly health, Surabaya City Health Office in 2014 recorded hypertension that occurs in the elderly as much as 19.56%. In the last data of elderly people with hypertension in February 2018 at Kebonsari Public Health Center there are 300 cases of men as many as 113 people and women 187 people.  The purpose of this study was to determine the effect of elderly gymnastics and walking on the decrease in blood pressure in elderly people with hypertension. The type of research used is Quasi Experimental Design. By using two-group pre-test post-test design. Instrument research in the form of elderly gymnastics and walking with duration 40 to 50 minutes done 3 times a week for 1.5 months. The test instrument measures blood pressure using a Spygmomanometer. Analysis of data used to process the results of research using t test (paired sample t-test) with a significant level of 0.05. Based on the results of the calculations have been done using SPSS application 22. Group gymnastics elderly average first tests and last tests systolic 163.1 mmHg to be 136 mmHg. On diastolic 108.9 to be 82 mmHg. While on group walk average first tests and last tests systolic 164.8 mmHg became 145.4 mmHg. On diastolic 106.9 became 90.2 mmHg. The results of this is research, there is a decrease in blood pressure in elderly and group gymnastics group walk on the elderly hypertension sufferers. It's just on a group of elderly blood pressure drop gymnastics is larger than the Group walk that small. Keywords: Hypertension, Gymnastic elderly, Walking, Blood pressure.